MODEL PENEGAKAN HUKUM TINDAK PIDANA PERSETUBUHAN TERHADAP ANAK BERBASIS SCIENTIFIC CRIME INVESTIGATION (STUDI KASUS DI WILAYAH HUKUM POLRES BIMA KOTA) - Mufti Alhikmatiar; Erham Erham; Andriadin Andriadin (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
The crime of sexual intercourse with a minor is a serious offense requiring evidence-based law enforcement to ensure accurate proof and optimal protection for victims. This study aims to analyze the application of Scientific Crime Investigation (SCI) in investigations of such crimes within the jurisdiction of the Bima City Police, identify legal, technical, institutional, and sociocultural obstacles, and formulate an SCI-based law enforcement model suited to the local community's characteristics. The research employs a socio-legal (empirical-legal) approach with a case study design. Data were gathered through in-depth interviews with investigators from the Women and Children Protection Unit, forensic physicians, forensic psychologists, and prosecutors, supplemented by document analysis and field observations. Data were analyzed qualitatively involving reduction, presentation, and conclusion drawing utilizing source and method triangulation. The findings indicate that SCI implementation has not been optimal due to limited forensic facilities and personnel, ineffective inter-agency coordination, and a strong culture of resolving cases through amicable family settlements, which hinders the scientific evidentiary process. The novelty of this research lies in the formulation of an integrative law enforcement model that combines scientific investigation, cross-sectoral institutional strengthening, and an approach rooted in local wisdom to enhance investigative effectiveness within resource-constrained district police units. The study recommends strengthening forensic human resource capacity, developing comprehensive technical guidelines for the implementation of Scientific Crime Investigation (SCI), and establishing integrated forensic services at the regional level. These findings are expected to enrich the development of criminal law particularly regarding child protection and serve as a reference for formulating policies and standard operating procedures for evidence-based investigations. Keywords: Law Enforcement; Statutory Rape; Scientific Crime Investigation; Scientific Evidence; Bima City Police.